2015
DOI: 10.1007/s00167-015-3881-4
|View full text |Cite|
|
Sign up to set email alerts
|

Unconstrained total knee arthroplasty in significant valgus deformity: a modified surgical technique to balance the knee and avoid instability

Abstract: Adequate correction of valgus knee deformity was successfully achieved using this modified technique with satisfactory medium-term outcome and avoidance of instability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, other authors were also able to obtain satisfactory outcomes on more severely deformed knee. 6,19,27 Even though in this study the revision rate was available only over a short period of time, it is worthy to mention that also Sorrels et al 26 obtained comparable revision rate using cementless low contact stress (LCS) mobile bearing design; however, they were not able to obtain a systematically corrected alignment, which was instead achieved most of the times in the present study.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Furthermore, other authors were also able to obtain satisfactory outcomes on more severely deformed knee. 6,19,27 Even though in this study the revision rate was available only over a short period of time, it is worthy to mention that also Sorrels et al 26 obtained comparable revision rate using cementless low contact stress (LCS) mobile bearing design; however, they were not able to obtain a systematically corrected alignment, which was instead achieved most of the times in the present study.…”
Section: Discussionmentioning
confidence: 52%
“…Czekaj et al 6 additionally obtained a survival rate at ten years of 98.6% with severe deformities using a low-constraint deep-dish mobile bearing implant design, showing a high reliability of ultra-congruent mobile bearing prosthesis for malaligned knees. On the other hand, other studies are specific to severe valgus deformities such as Tucker et al 27 and Pagoti et al 19 who both reported satisfactory results using unconstrained mobile inserts.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…A cementless CORAIL stem and a cementless Pinnacle cup (DePuy Synthes, Warsaw, IN) were used in all THRs, which were performed via the posterior approach using a 12- to 14-cm incision [29]. Cementless LCS implants (DePuy Synthes, Warsaw, IN) were used for all TKRs via a medial Insall approach under tourniquet, released at capsule closure [30], [31]. Cementless Oxford Microplasty medial unicompartmental implants (Biomet Ltd., Bridgend, UK) were used for all UKRs via a distal medial parapatellar approach under tourniquet, released at capsule closure [32].…”
Section: Methodsmentioning
confidence: 99%
“…In the first 8 years of this series the incidence of spinout was 0.58%; during this period the authors routinely released collateral ligaments in both varus and valgus knees to achieve soft-tissue balance in extension. In the last 16 years they stopped releasing the collateral ligaments [ 9 , 10 ] and the incidence fell to 0.2% (12 out 5994).…”
Section: Introductionmentioning
confidence: 99%